Synthesizing electrical drive control system with several sliding surface reaching laws applied to manipulate Quadcopter - Lê Khánh Thành; Vũ Quốc Huy (Journal of Military Science and Technology, 2024)
This paper studies on the stability of a variable structure control system operating in sliding mode using Lyapunov criteria and different sliding surface reaching speeds. This is a new research result that allows quantifying sliding surface parameters thanks to the system’s settling time and desired error. The paper also proposes a method for synthesizing a variable structure controller using a general sliding surface approach law and specifying some derivatives of the general sliding surface reaching law. Some simulations of controlling a Quadcopter motion channel have been performed in Matlab to demonstrate the proposed research results.